Mapping Vegetation Condition Before and After the 2025 Flood Using Sentinel-2-Based NDVI in Pidie Jaya Regency - Nela Wirja; Muhammad Nanda; Deviyani Rusdiyanti Putri; Mulia Rahmi; Nurul Azmi (Jurnal Serambi Engineering, 2026)
The major flood that affected Pidie Jaya Regency in November 2025 caused substantial changes in land-surface conditions, including vegetation and agricultural areas. However, spatial information on vegetation conditions before and after the flood remains limited. This study aimed to assess spatial patterns of vegetation conditions before and after the 2025 flood in Pidie Jaya Regency, Aceh Province, using the Normalized Difference Vegetation Index (NDVI) derived from Sentinel-2 imagery. Sentinel-2 Surface Reflectance (Level-2A) imagery was processed using the Google Earth Engine (GEE) platform. Imagery acquired during 1 October–25 November 2025 was used to represent pre-flood conditions, while imagery acquired during 26 November–15 December 2025 was used to represent post-flood conditions. Images from each period were composited using the median value, and NDVI was calculated from the Red (Band 4) and Near-Infrared (NIR; Band 8) bands. The results revealed heterogeneous spatial patterns of NDVI response. The Southern area of Meureudu, Meurah Dua, and Ulim Districts showed apparent shifts from areas with relatively high pre-flood NDVI values (0.6–1.0) toward lower NDVI classes (0.2–0.5) after the flood. This pattern is consistent with vegetation disturbance and changes in land-surface conditions associated with flooding. In contrast, several northern lowland areas exhibited an increase in NDVI from approximately 0.0–0.2 to 0.3–0.5. This increase does not necessarily indicate vegetation recovery but may be associated with changes in surface conditions, moisture, and the deposition and subsequent drying of flood sediments.